LEGAL REFORM (TRADE) SPECIAL STUDY ON THE NEED FOR THE ANTI MONOPOLY ACT OR UNFAIR BUSINESS COMPETITION POST THE JOB CREATION LAW - Enjum Jumhana; Achmad Nashrudin Priatna (Nindikayla Institute, 2023)
The business world is inseparable from fair and reasonable competition in business activities, so there is no central economic power for certain business sectors while remaining obedient to existing laws and regulations. Law Science does not see chaos but rather as a component of a system with a bond of legal principles. As a legal system, it contains orders and rules which constitute a unified whole of parts or elements that are interrelated to one another. In principle, in order to obtain maximum revenue, the business area is normal behavior as long as there are no monopolistic practices, but in reality, it is always colored by the power of unfair competition groups. Therefore it is not easy to interpret the meaning and causes of monopolistic practices which are the implementation of Law No.5Â ofÂ 1999 which are directly re-lated to business activities as well as the economy of a nation